PHYTOCHEMICAL AND ANTIMICROBIAL SCREENING OF THE LEAF AND ROOT BARK EXTRACTS OF CALOTROPIS PROCERA (Air) (Biological Sciences - PJSIR, 2002)
The antimicrobial activity of the cold methanolic extracts of the leaf and root bark of Calotropis pr ocera (Ait) , (Fam: Asclepiadaceae) was determined using the agar diffusion method . Staphylococcus aureus, Escherichia coli,  Candida  albicans, Pseudomona s aeruginosa, Klebsiella aerogenes and Enterobact er aerogenes were used as test organisms. Antimicrobial activity was observed with the leaf extract on four of the organisms tested , while the  root  bark  showed  activity on only two of the test organisms. The minimum inhibitory  concentration  (MIC)  for  the  positively  tested  organisms lie within the range of 10-50 mg  mi-1.  Phytochemical  analysis  conducted  on the samples revealed  the  presence of saponins, glycosides, and simple sugars in the leaves, while the root bark was found  to contain  tannins  in  addition  to  these groups . Fractionation  of  the  crude  extract  by  solvent-solvent  extraction  procedure  indicated  that  the  organic  acidic and organic  basic  fractions were  more active. Infra-red  (IR) spectroscopy of the two factions indicated  the presence  of carboxylic  acids and  carbonyl  groups.  The  findings  of this  study conforms  with  the local  use of the  plant.